Early neonatal outcome of preterm babies with absent or reverse end diastolic flow in antenatal doppler velocimetry - Kannan, Mohanraj; L. G., Aishwarya Lakshmi; P. G., Rajakumar; R., Selvaraj (International Journal of Contemporary Pediatrics, 2021)
Background: Preterm babies with abnormal doppler velocimetry during second and third trimesters of pregnancy pose various early neonatal morbidities like recurrent hypoglycaemia, feed intolerance and prolonged hospital stay. In our study we compared the incidence of hypoglycaemia, feed intolerance, risk of necrotising enterocolitis (NEC) and length of hospital stay among preterm babies with abnormal doppler flow to the gestational age matched preterm babies with normal umbilical artery doppler flow velocimetry. Methods: 30 preterm babies who had abnormal umbilical artery flow during their last antenatal doppler scan were included as study group and gestational age matched 30 preterm babies who had normal doppler study had been taken as controls. The incidence of hypoglycaemia, feed intolerance, NEC, length of hospital stay had been compared between two groups. Results: The case group with abnormal umbilical artery doppler had increased incidence of hypoglycaemia (15 of 30 babies in case versus 5 of 30 babies in control) which was statistically significant. Feed intolerance, necrotizing enterocolitis and length of hospital stay were all significantly increased in preterm babies with abnormal umbilical artery doppler when compared to preterm babies with normal umbilical artery doppler flow. Conclusions: Preterm babies with abnormal umbilical artery doppler were at increased risk of hypoglycaemia, feed intolerance, NEC and prolonged hospital stay. Knowledge on this is important to monitor closely for hypoglycaemia, gradually increase feeds and explain parents about expected morbidities which can increase the length of hospital stay in neonatal intensive care unit (NICU).